7 FREE BEST OPEN SOURCE DATABASE MANAGEMENT SYSTEMS - Dots. Abdumanap Abdukarimov; Assist. Abror Rashidov R (Journals Park Publishing, 2022)
IT departments work with a meager budget. Therefore, reducing costs will allow the company not only to stay afloat, but also to direct the saved funds to development. In order to use the available budget more efficiently, we will be acquainted with seven free systems that allow the development and management of databases and open source DBM solutions.
Keywords: CUBRID, Firebird, Software for working with MariaDB database, MongoDB